Leveraging Openness for Refugees’ Higher Education: A Freiran Perspective to Foster Open Cooperation - Barbara Class; Thierry Agagliate; Abdeljalil Akkari; Naoufel Cheikhrouhou; Moussa Sagayar (Open Praxis)
Research in the field of Higher Education in Emergencies (HEiE) starts to question the imposed Global North-centred perspective which arrives with ready-made solutions, considering refugees as objects of intervention rather than subjects of transformation.